Early recognition and management of septic shock in children - Paolo Biban; Marcella Gaffuri; Stefania Spaggiari; Federico Zaglia; Alessandra Serra; Pierantonio Santuz (Pediatric Reports, 2012)
Septic shock remains a major cause of morbidity and mortality among children, mainly due to acute haemodynamic compromise and multiple organ failures. In the last decade, international guidelines for the management of septic shock, as well as clinical practice parameters for hemodynamic support of pediatric patients, have been published. Early recognition and aggressive therapy of septic shock, by means of abundant fluid resuscitation, use of catecholamines and other adjuvant drugs, are widely considered of pivotal importance to improve the short and long-term outcome of these patients. The aim of this paper is to summarize the modern approach to septic shock in children, particularly in its very initial phase, when pediatric healthcare providers may be required to intervene in the pre-intensive care unit setting or just on admission in the pediatric intensive care unit.